Representation in Religion, Studies in Honor of Moshe Barasch. - Jan Assmann; Albert I. Baumgartner (Editors) (Numen Book Series, 2001)
The role of representation in religion is complex. While often perceived as essential, it is also associated in many traditions with the liability of idolatry and provokes iconoclasm. The essays in this volume examine the nuances of representation in religion and the debate concerning its place across a variety of traditions from the three Abrahamic faiths, to those of antiquity and the East. This volume consists of presentations made at an international conference held in honor of Moshe Barasch, art historian and cultural critic, who has done much to elucidate the light which representation and religion shed on each other. It pays tribute to Barasch by expanding the base of understanding and insight he has erected. It should be of interest to students of religion and of art history.